Microplastics Content of Seaweeds in the Mariculture Potential Zone at The Southwest of Coastal Bawean Island - Wiga Alif Violando; Nur Maulida Safitri; Andi Rahmad Rahim; Mauludiyah; Agus Purnomo Ahmad Putikadyanto (Jurnal Biologi Tropis, 2023)
Bawean Island is a sheltered and clean coastal waters that can be exploited for mariculture, particularly seaweed. Due to its enclosed environment, the presence of different wastes, particularly microplastics, is deemed negligible. The purpose of this research is to investigate the prevalence of microplastics in numerous seaweeds on Bawean Island's southwest shore, as well as the viability of seaweed production. At a depth of 1-6 meters, samples of red, green, and brown seaweed were obtained and examined for microplastics by destroying the cell walls. At the two observation sites, water characteristics such as current, pH, salinity, TDS, DO, substrate, temperature, depth, and brightness were also monitored. Based on the results, the southwest coastal waters of Bawean were suitable for seaweed cultivation. Furthermore, the lowest-highest microplastic concentration was discovered in Gracillaria sp. 44±18 particles/100g, Halimeda sp. 52±16 particles/100g, Caulerpa sp. 94±31 particles/100g, and Sargassum sp. 251±59 particles/100g, with a form of microplastic found in fragments, fibers, and films. Various colors of microplastics were found. According to this study, seaweed can act as a vector for microplastics to infiltrate the food chain. This is indicated by the substantial accumulation of microplastics in cultivation potential zones of seaweed where there are fewer human activities. This microplastic accumulation could then occur at a higher trophic level, thus seaweed in nature must be quarantined and cleaned after cultivation to reduce the concentration of microplastic contamination.